2017
DOI: 10.1002/asi.23732
|View full text |Cite
|
Sign up to set email alerts
|

Connecting theory and practice in digital humanities information work

Abstract: The omnipresence and escalating efficiency of digital, networked information systems alongside the resulting deluge of digital corpora, apps, software, and data has coincided with increased concerns in the humanities with new topics and methods of inquiry. In particular, digital humanities (DH), the subfield that has emerged as the site of most of this work, has received growing attention in higher education in recent years. This study seeks to facilitate a better understanding of digital humanities by studyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…At postgraduate research levels (MRes/PhD), specialization increases further, evidenced by research done in the areas of digital humanities and cultural informatics (Klein & Gold, ). Growth in pedagogy in cultural and design informatics, and digital humanities, is suggested to trail farther behind the research developments within the field (Clement & Carter, ; Klein & Gold, ; Poole, ). The findings of our research depict a similar picture, especially at the undergraduate level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At postgraduate research levels (MRes/PhD), specialization increases further, evidenced by research done in the areas of digital humanities and cultural informatics (Klein & Gold, ). Growth in pedagogy in cultural and design informatics, and digital humanities, is suggested to trail farther behind the research developments within the field (Clement & Carter, ; Klein & Gold, ; Poole, ). The findings of our research depict a similar picture, especially at the undergraduate level.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, according to Robinson et al (), the common interests between the fields lie in digitization, preservation, repositories, metadata, visualization, and so on; hence the fields reinforce each other. It is necessary to explore the pedagogy available within this area, as it is suggested that pedagogy in digital humanities and cultural informatics has not grown as much as it has in research (Bail, ; Clement & Carter, ; Jones, ; Klein & Gold, ; Poole, ). However, as mentioned below, this is not the focus of this study.…”
Section: Introductionmentioning
confidence: 99%
“…By harnessing data, computational networked information systems extend revolutionary possibilities for collaborative, interdisciplinary, and distributed humanities scholarship (Berry, ; Borgman, , ; Clement & Carter, ; Evans & Rees, ; Manovich, ). Even so, exploiting big data for humanities research does not negate the value of more traditional historical sources or research questions and methods (Gibbs & Owens, ; Owens, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The field remains capacious, embracing information practices such as archiving, quantitative analysis, tool‐building, visualization, 3D modeling, sonification, curation, manipulation, interpretation, editing, modeling, mapping, reading, mining, gaming, remixing, publishing, critiquing, collaborating, code studies, and databases—often at unprecedented scale and scope (Burdick, ; Davidson, ; Hayles, ; Klein & Gold, ; Poole, , ; Trace & Karadkar, ). Often trained in traditional disciplines, DH scholars may occupy traditional faculty positions, but in addition to or instead of these positions, many undertake hybrid information work involving a wide range of digital data, resources, methods, activities, and tools (Clement & Carter, ; Given & Willson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Information DOI: 10.1002/pra2.284 83rd Annual Meeting of the Association for Information Science & Technology October 25-29, 2020. Author(s) retain copyright, but ASIS&T receives an exclusive publication license professionals have been discussed as key contributors to these infrastructures (Clement & Carter, 2017;Poole, 2017), not only for their technical skills but also for project management (Tabak, 2017) and for teaching and training others (Rasmussen, Croxall, & Otis, 2017), often across disciplines (Senchyne, 2016;Terras, 2012).…”
Section: Descriptionmentioning
confidence: 99%